Education and society in St. Kitts and Nevis - Halliday, Joseph Jacob (Institute of Social and Economic Research, UWI, 1991)
This paper provides a historical perspective of education in the context of the pre- and immediate post-emancipation era in St. Kitts and Nevis, showing the interaction of church and school to accomplish the aims and objectives of that society, and how other organizations like the trade union movement impacted upon society. The issue of fragmentation and regionalism in the Caribbean is discussed, since the pull or push towards insularity and integration movement either credited or influenced existing educational institutions and programmes. The education system of St. Kitts and Nevis is outlined, as indicative of an attempt to show how one particular mini-state has endeavoured to respond to certain aspects of educational problems in a Caribbean setting
Keywords: Sociology of education